NUCLEAR SAFETY AND RADIOLOGICAL PROTECTION IN POLAND - Kleszcz Sławomir (2021)
Purpose: This paper aims to present the nuclear security and radiological protection system in Poland. Method: The scientific methods used in this paper include critical analysis of literature as well as analysis and logical construction method. The research was conducted based on data relating to the Polish Armed Forces. Results: The article presents selected issues related to radiation security in the state defence system. It explains the essence of this problem. It presents entities responsible for the implementation of tasks related to nuclear safety and radiological protection in Poland, as well as legal acts that regulate these aspects of state security. Conclusions: The issue in questions has huge implications for both the natural and medical sciences, as well as for the psychological aspects. Compliance with strict safety requirements and work regulations is crucial for protecting workers’ health and life and, in particular, the security of millions of citizens, as one of the biggest radiation disasters in the world history, the Chernobyl disaster in 1986, may prove. Rising some kind of public awareness and education in the area of radiation security is also extremely important. The society needs to understand the problem and then accept it as an inevitable process in building a new national power industry.